2015
DOI: 10.1111/jnc.13022
|View full text |Cite
|
Sign up to set email alerts
|

Substantially elevating the levels of αB‐crystallin in spinal motor neurons of mutant SOD1 mice does not significantly delay paralysis or attenuate mutant protein aggregation

Abstract: There has been great interest in enhancing endogenous protein maintenance pathways such as the heat-shock chaperone response, as it is postulated that enhancing clearance of misfolded proteins could have beneficial disease modifying effects in ALS and other neurodegenerative disorders. In cultured cell models of mutant SOD1 aggregation, co-expression of αB-crystallin (αB-crys) has been shown to inhibit the formation of detergent-insoluble forms of mutant protein. Here, we describe the generation of a new line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Notably, it was recently shown that overexpressing the chaperone protein hsp110 in neurons extends the survival of SOD1 G85R -YFP and SOD1 G93A mice (51). However, altering the expression levels of other chaperones previously linked to SOD1, including hsp70, hsp90, hsp27, and αB-crystallin, failed to significantly affect the disease course in different mutant SOD1 mouse models (52)(53)(54)(55)(56).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, it was recently shown that overexpressing the chaperone protein hsp110 in neurons extends the survival of SOD1 G85R -YFP and SOD1 G93A mice (51). However, altering the expression levels of other chaperones previously linked to SOD1, including hsp70, hsp90, hsp27, and αB-crystallin, failed to significantly affect the disease course in different mutant SOD1 mouse models (52)(53)(54)(55)(56).…”
Section: Discussionmentioning
confidence: 99%
“…Only ALDH2 and CRYAB are consistently differentially regulated between spinal cord and muscle samples for stress response. αB-crystallin (CRYAB) has been extensively studied as a potential treatment for ALS treatment, because over-expression reduced SOD1 aggregates in cell culture models and knockout in SOD1 mutant mice accelerated disease onset (Xu et al, 2015). However, transgenic overexpression of αB-crystallin in SOD1 mutant mouse lines did not slow disease progression or reduce aggregate formation, making it a poor therapeutic target for ALS (Xu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…; Xu et al . ). Thus, it remains to be determined whether up‐regulating chaperone levels is a valid therapeutic approach for the treatment of these neurodegenerative diseases.…”
Section: The Role Of Molecular Chaperones In Neurodegenerative Diseasementioning
confidence: 97%
“…Nevertheless, various studies have demonstrated that over-expression of the HSPs can prevent the aggregation and associated toxicity of disease-related proteins, for example, amyloid-b (Hoshino et al 2011), polyglutamineexpanded proteins (Wyttenbach et al 2002;Jiang et al 2012;Ormsby et al 2013); a-synuclein (Auluck et al 2002;McLean et al 2002;Tue et al 2012;Cox et al 2014) (Auluck et al 2002;McLean et al 2002;Tue et al 2012;Cox et al 2014), and superoxide dismutase 1 (Koyama et al 2006;Crippa et al 2010;Novoselov et al 2013); proteins implicated in the pathogenesis of AD, HD, PD, and ALS, respectively. However, others have reported that overexpression of some HSPs has no significant effects on disease progression in mouse models of disease (e.g., Liu et al 2005;Krishnan et al 2008;Shimshek et al 2010;Xu et al 2015). Thus, it remains to be determined whether upregulating chaperone levels is a valid therapeutic approach for the treatment of these neurodegenerative diseases.…”
Section: The Role Of Molecular Chaperones In Neurodegenerative Diseasementioning
confidence: 99%